THE RELATIONSHIP BETWEEN THE COGNITIVE FACTOR AND SOCIAL ENVIRONMENT WITH HIV/AIDS CHECK-UP ACTIVENESS RATES AMONG CROSS-DRESSERS IN GORONTALO - Herlina Jusuf; Amanda Adityaningrum; Nikmatisni Arsad (UNG, 2023)
In Gorontalo, the total number of HIV/AIDS cases in June 2021 is 64, and homosexuals occupy the highest position, with 34 patients. The term “homosexuals” is historically used to diagnose medical/mental illnesses, and cross-dresser is an alternative term to replace it. The number of cross-dressers in Gorontalo is around 350. Based on the CDC, an HIV check-up is the first step in getting care, treatment, and controlling the disease for people living with HIV and keeping others safe. The novelty in this study was to see the relationship between cognitive factors and the social environment with HIV/AIDS check-up activeness rates among cross-dressers in gorontalo. This research aims to determine the significant relationship between the cognitive factor and the social environment with the activeness of HIV/AIDS examinations in cross-dressers in Gorontalo, Indonesia. The population is 60 people and the sample is 52 cross-dressers. Independent variables used are the cognitive factor (knowledge and attitude) and social environment (support from fellow cross-dressers), while the dependent variable is the HIV/AIDS check-up activeness rates among cross-dressers. This research found that most of the respondents were cross-dressers aged between 25 and 29 years and participants mostly went to Community Health Center for HIV/AIDS check-ups. However, some participants did not go or find out how to do the HIV/AIDS check-up. The conclusion that cognitive factor (knowledge and attitude) was not associated with HIV/AIDS check-up activeness rates among cross-dresser because they failed to reject the null hypothesis. In comparison, social environment (support from fellow cross-dressers) was associated with HIV/AIDScheck-up activeness rates among cross-dressers because it rejected the null hypothesis.